ChemInform Abstract: Advances in the Chemistry of Quinoxalinone Derivatives. Issue 21 (May 2015) - Shi, Leilei; Zhou, Hua; Wu, Jifeng; Li, Xun
Abstract Review: methods for the synthesis of quinoxalinone derivatives with emphasis on facile and eco‐friendly protocols; 44 refs.